2013
DOI: 10.1152/ajpregu.00395.2012
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-based therapies for angiotensin II-associated cardiovascular diseases

Abstract: Cardiovascular diseases, including hypertension and heart failure, are associated with activation of the renin-angiotensin system (RAS) and increased circulating and tissue levels of ANG II, a primary effector peptide of the RAS. Through its actions on various cell types and organ systems, ANG II contributes to the pathogenesis of cardiovascular diseases by inducing cardiac and vascular hypertrophy, vasoconstriction, sodium and water reabsorption in kidneys, sympathoexcitation, and activation of the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 158 publications
1
51
0
2
Order By: Relevance
“…Ang II is a crucial factor responsible for hypertension and cardiovascular disease [6,26]. Recently, some studies have focused on exploring the effect of Ang II on endothelial cells [27,28,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II is a crucial factor responsible for hypertension and cardiovascular disease [6,26]. Recently, some studies have focused on exploring the effect of Ang II on endothelial cells [27,28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (Ang II) is a key independent risk factor of hypertension, inducing cardiovascular disease development [5,6]. Many reports have suggested that Ang II stimulates nicotinamide adenine dinucleotide phosphate generation in the vascular cell.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin (Ang) II, an important mediator of the renin-angiotensin system (RAS), directly promotes myocardial hypertrophy, hypertension, and interstitial fibrosis [2]. There are two Ang II receptor subtypes: angiotensin II type 1 receptor (AT1-R) and angiotensin II type 2 receptor (AT2-R).…”
Section: Introductionmentioning
confidence: 99%
“…4 However, the use of anti-oxidants as a therapeutic/preventive tool is still debated. 5,6 In addition, a predisposing factor for atherosclerosis is most definitively regarded to be a hypertensive state. 7 Given the uniqueness of the composition of sturgeon eggs as compared to other marine species regarding polyunsaturated fatty acids (PUFAs) and phospholipid moieties, 8 and in consideration of our recent work proving the efficacy of a controlled caviar-derived homogenate, LD-1227 (Caviarlieri, LabDom, Switzerland), as an anti-oxidant/antiinflammatory modulator with a wider efficacy properties as compared to docosahexaenoic acid (DHA), 9,10 we also tested this compound on the ultrastructure of the SHR aorta.…”
Section: Introductionmentioning
confidence: 99%